Iridium‐Catalyzed ortho‐Selective Borylation of Aromatic Amides Enabled by 5‐Trifluoromethylated Bipyridine Ligands. Issue 18 (24th January 2023) - Marcos‐Atanes, Daniel; Vidal, Cristian; Navo, Claudio D.; Peccati, Francesca; Jiménez‐Osés, Gonzalo; Mascareñas, José L.
Abstract: Iridium‐catalyzed borylations of aromatic C−H bonds are highly attractive transformations because of the diversification possibilities offered by the resulting boronates. These transformations are best carried out using bidentate bipyridine or phenanthroline ligands, and tend to be governed by steric factors, therefore resulting in the competitive functionalization of meta and/or para positions. We have now discovered that a subtle change in the bipyridine ligand, namely, the introduction of a CF3 substituent at position 5, enables a complete change of regioselectivity in the borylation of aromatic amides, allowing the synthesis of a wide variety of ortho ‐borylated derivatives. Importantly, thorough computational studies suggest that the exquisite regio‐ and chemoselectivity stems from unusual outer‐sphere interactions between the amide group of the substrate and the CF3 ‐substituted aryl ring of the bipyridine ligand. Abstract : The mere introduction of a CF3 group at position 5 of a bipyridine ligand promotes a dramatic change in regioselectivity in the iridium‐catalyzed borylation of benzamides and derivatives, from meta / para to ortho ‐substitution. Computational and experimental data suggest that this effect is associated with unusual outer‐sphere dispersion interactions between the carbonyl group of the substrate and the CF3 ‐bipy ring of the ligand.